Evaluation of Ecosystem-Based Small Pelagic Fisheries Management in Fish Resources Domains in North Sulawesi Waters as a Blue Economy Implementation - Lasabuda, Ridwan; Wagey, Billy Theodrus; Kondoy, Khristin I.F (Jurnal Ilmiah PLATAX, 2026)
This study evaluates the management of small pelagic fisheries, specifically focusing on the mackerel scad (Decapterus macarellus), in North Sulawesi waters through the Ecosystem Approach to Fisheries Management (EAFM) framework within the Fish Resources Domain. Conducted at PPP Tumumpa, Manado, between March and November 2025, the research utilized surveys, interviews, and literature reviews. Performance was assessed using Multi-Criteria Analysis (MCA) across six key indicators: standardized CPUE, fish size trends, juvenile proportion, species composition, range collapse, and ETP (Endangered, Threatened, and Protected) species. The results indicate that management performance is highly effective, with a composite value of 85, placing it in the "Very Good" category. Key findings include a stable standardized CPUE (score 3) and a low proportion of juvenile catch at less than 30% (score 3),,. Other indicators, such as fish size trends, catch composition, and ETP species management, showed stable or moderate performance (score 2). These results demonstrate that fishery management in the region aligns with Blue Economy principles, ensuring sustainable resource utilization while maintaining ecosystem health. Keywords: small pelagic, North Sulawesi waters, EAFM, fish resource domain, blue economy Abstrak. Studi ini mengevaluasi pengelolaan perikanan pelagis kecil, khususnya ikan kembung (Decapterus macarellus), di perairan Sulawesi Utara melalui kerangka Pendekatan Ekosistem untuk Pengelolaan Perikanan (EAFM) dalam Domain Sumber Daya Ikan. Dilakukan di PPP Tumumpa, Manado, antara Maret dan November 2025, penelitian ini menggunakan survei, wawancara, dan tinjauan pustaka. Kinerja dinilai menggunakan Analisis Multikriteria (MCA) di enam indikator utama: CPUE standar, tren ukuran ikan, proporsi juvenil, komposisi spesies, penurunan jangkauan, dan spesies ETP (Terancam Punah, Terancam, dan Dilindungi). Hasil menunjukkan bahwa kinerja pengelolaan sangat efektif, dengan nilai komposit 85, menempatkannya dalam kategori "Sangat Baik". Temuan utama meliputi CPUE standar yang stabil (skor 3) dan proporsi tangkapan juvenil yang rendah di bawah 30% (skor 3). Indikator lain, seperti tren ukuran ikan, komposisi tangkapan, dan pengelolaan spesies ETP, menunjukkan kinerja yang stabil atau moderat (skor 2). Hasil ini menunjukkan bahwa pengelolaan perikanan di wilayah tersebut selaras dengan prinsip-prinsip Ekonomi Biru, memastikan pemanfaatan sumber daya yang berkelanjutan sambil menjaga kesehatan ekosistem. Kata kunci: ikan pelagis kecil, perairan Sulawesi Utara, EAFM, domain sumber daya ikan, ekonomi biru